USE OF RATING SYSTEM IN THE TEACHING OF PHYSICAL EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
Grading is a basic method of the credit-modulus system. The experiment has the analysis of accumulation of grades analyzing different results of the credit-modulus system of the scheme "Track and field athletics and methods of teaching" for the I semester. The increasing interest o f students in the ultimate result completes more conscious and active attitude towards educational activity.